InSight Pressure Data Recalibration, and Its Application to the Study of Long‐Term Pressure Changes on Mars. Issue 5 (23rd May 2022) - Lange, L.; Forget, F.; Banfield, D.; Wolff, M.; Spiga, A.; Millour, E.; Viúdez‐Moreiras, D.; Bierjon, A.; Piqueux, S.; Newman, C.; Pla‐García, J.; Banerdt, W. B.
Abstract: Observations of the South Polar Residual Cap suggest a possible erosion of the cap, leading to an increase of the global mass of the atmosphere. We test this assumption by making the first comparison between Viking 1 and InSight surface pressure data, which were recorded 40 years apart. Such a comparison also allows us to determine changes in the dynamics of the seasonal ice caps between these two periods. To do so, we first had to recalibrate the InSight pressure data because of their unexpected sensitivity to the sensor temperature. Then, we had to design a procedure to compare distant pressure measurements. We propose two surface pressure interpolation methods at the local and global scale to do the comparison. The comparison of Viking and InSight seasonal surface pressure variations does not show changes larger than ±8 Pa in the CO2 cycle. Such conclusions are supported by an analysis of Mars Science Laboratory (MSL) pressure data. Further comparisons with images of the south seasonal cap taken by the Viking 2 orbiter and MARCI camera do not display significant changes in the dynamics of this cap over a 40 year period. Only a possible larger extension of the North Cap after the global storm of MY 34 is observed, but the physical mechanisms behind this anomaly are not well determined. Finally, the first comparison of MSL and InSight pressure data suggests a pressure deficit at Gale crater during southern summer, possibly resulting from a large presence of dust suspended within the crater. Plain Language Summary: Observations of the permanent CO2 ice cap at the south pole of Mars in the 2000s suggested that the cap was eroding, possibly releasing a significant amount of CO2 into the atmosphere. To test this hypothesis, we compare surface pressures recorded by Viking in the 1970s and those recorded by InSight in 2018–2021 to confirm or refute the suspected increase of the atmospheric mass. After establishing our comparison method, we correct the influence of the sensor temperature on the InSight pressure data, which was discovered during our investigation. Comparison of the pressure data, as well as images of the seasonal caps taken by orbiters, do not reveal any change in the atmospheric mass or the dynamics of the seasonal ice caps that develop during the martian year. These conclusions are reinforced by reanalyzing the pressure data recorded by the Curiosity rover. Only small interannual changes are observed, potentially related to the effect of the dust storms that happened on Mars between 2016 and 2018. Finally, we report a possible pressure deficit at MSL's location during southern hemisphere summer, potentially explained by the unusual presence of dust in the crater air. Key Points: We propose a recalibration of InSight pressure data to correct an unexpected sensitivity to the sensor temperature A comparison between the InSight and Viking 1 pressure data does not show variations larger than ±8 Pa in the global atmospheric mass This comparison also supports the absence of long‐term variability in the dynamics of seasonal cap formation and sublimation